Exploring Performance-Based Approach in Academic Writing Courses in Higher Education - R, Abdul Rahman; Saud, Syukur; Ramadhani, Ahmad Arkam; Saud, Chaerul Fadlan (Universitas Negeri Makassar, 2025)
Abstract. A teacher or lecturer are better able to foster students’ potential and abilities reflected in their academic output when students are actively engaged in the learning process. This highlights the need for instructional content that integrates student performance in alignment with learning goals. The Performance-Based Approach (PBA) serves as an effective means of linking students’ ongoing performance to their final academic outcomes. In the context of an Academic Writing course that applied PBA, students were expected to produce a draft research proposal suitable for seminar presentation upon course completion. This study adopted a case study research design to gain in-depth insights into the participants’ experiences. The findings reveal that students responded positively to the use of PBA in the learning process. The implementation of Performance-Based Approach significantly enhanced the quality of instruction, as evidenced by students’ enthusiastic engagement. Overall, PBA proved to be a highly effective strategy for improving learning outcomes in academic writing instructionKeywords: Academic writing, process Approach, Performance-Based Assessment